Who has the power? Manipulating and reclaiming social support in solitary confinement - Gonzalez, Gabriela (Punishment & society, 2025)
Social support is often cited as among the most important factors in successful adjustment to prison, reentry, and overall desistance. Yet, few studies have sought to explore the impact of familial social support on incarcerated persons’ experiences in solitary confinement. Analyzing the narratives of men housed in isolation units in one Northwestern state, the present study identifies the variety of experiences they have with social support during isolation, particularly focusing on the prison’s role in structuring relationships between incarcerated persons and their loved ones. Findings reveal that standard communication restrictions in solitary confinement have disparate impacts on differently situated persons living in prisons. Those who are able to maintain familial attachments are able to cope with isolation, first, by maintaining roles in prosocial webs, and second, by accessing material and emotional support, advocacy, and psychological stability. In spite of these benefits, policies and procedures in solitary confinement exacerbate the imprisonment experience and yield negative consequences for prison life, health, family, and prison operations.